2023
DOI: 10.1111/pbi.14037
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of the NbCORE receptor drastically improves agroinfiltration productivity in older Nicotiana benthamiana plants

Abstract: Summary Nicotiana benthamiana is increasingly used for transient gene expression to produce antibodies, vaccines, and other pharmaceutical proteins but transient gene expression is low in fully developed, 6–8‐week old plants. This low gene expression is thought to be caused by the perception of the cold shock protein (CSP) of Agrobacterium tumefaciens. The CSP receptor is contested because both NbCSPR and NbCORE have been claimed to perceive CSP. Here, we demonstrate that CSP perception is abolished in 6‐week‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…To confirm that Nb CORE is required for detecting csp22, we depleted Nb CORE with Virus-induced Gene Silencing (VIGS) using Tobacco Rattle Virus (TRV) vectors carrying a 300bp fragment of Nb CORE, or of β-glucuronidase (GUS) as a negative control (Dodds et al, 2023). Oxidative burst assays showed that 6wk-old TRV::CORE plants are blind to csp22 of CspD, in contrast to TRV::GUS plants, which show an csp22-induced oxidative burst ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm that Nb CORE is required for detecting csp22, we depleted Nb CORE with Virus-induced Gene Silencing (VIGS) using Tobacco Rattle Virus (TRV) vectors carrying a 300bp fragment of Nb CORE, or of β-glucuronidase (GUS) as a negative control (Dodds et al, 2023). Oxidative burst assays showed that 6wk-old TRV::CORE plants are blind to csp22 of CspD, in contrast to TRV::GUS plants, which show an csp22-induced oxidative burst ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…Virus-induced gene silencing (VIGS) -N. benthamiana plants were silenced for NbCORE, SBT5.2, glucuronidase GUS (negative control) and phytoene desaturase PDS (positive control) were generated using VIGS as previously described (Dodds et al, 2023, Beritza et al, 2024. Briefly, overnight cultures of A. tumefaciens GV3101 were collected and resuspended in agroinfiltration buffer (10 mM MgCl2, 10 mM MES pH 5.0, and 100 mM acetosyringone).…”
Section: Lc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…Nb CORE, for instance, is an immune receptor that recognises cold shock proteins of Agrobacterium but is expressed only in older N. benthamiana plants (Wang et al ., 2016). Depletion of Nb CORE with virus‐induced gene silencing caused an eightfold higher transient green fluorescent protein (GFP) expression in older plants (Dodds et al ., 2023). Meanwhile, suppression of immune responses has been achieved with bacterial type‐III effector AvrPto, which inhibits immune‐related kinases (Xing et al ., 2007).…”
Section: Figmentioning
confidence: 99%